2016
DOI: 10.1161/hypertensionaha.116.07353
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Reverses Development of Pulmonary Hypertension via Aromatase Inhibition

Abstract: H uman pulmonary arterial hypertension (PAH) is a progressive disease of the pulmonary vasculature, which often leads to right heart failure. PAH is characterized by elevated pulmonary pressure (>25 mm Hg at rest), vascular remodeling, and occlusive pulmonary vascular lesions. Although survival rates are improving slowly; there remains an unacceptably poor survival rate. 1 Females are more susceptible to PAH than males, as indicated in, for example, the REVEAL (Registry to Evaluate Early and Long-Term PAH D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 49 publications
(74 reference statements)
8
77
2
1
Order By: Relevance
“…Administration of AN after Sugenhypoxia administration reduced RV systolic pressure, pulmonary vascular remodeling, and RV mass in the female animals (in whom it also reduced E2 levels). This group also showed that metformin had a similar effect via aromatase inhibition (17). Small muscular pulmonary arterioles also expressed estrogen receptor (ER)-a in the serotonin transporter overexpressing animal model, the blockade of which reduced RV systolic pressure (16).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Administration of AN after Sugenhypoxia administration reduced RV systolic pressure, pulmonary vascular remodeling, and RV mass in the female animals (in whom it also reduced E2 levels). This group also showed that metformin had a similar effect via aromatase inhibition (17). Small muscular pulmonary arterioles also expressed estrogen receptor (ER)-a in the serotonin transporter overexpressing animal model, the blockade of which reduced RV systolic pressure (16).…”
Section: Discussionmentioning
confidence: 92%
“…Finally, recent studies have shown that aromatase is produced in the smooth muscle cells of the small muscular pulmonary arteries in both female animal models of PH and in women with PAH (15,16). Administration of the aromatase inhibitor anastrozole (AN) reduced pulmonary arterial pressures, pulmonary vascular changes, and indexes of RV hypertrophy in experimental PH (15,16); metformin had similar effects via aromatase inhibition (17). Together, experimental and observational evidence suggests that limiting E2 exposure via aromatase inhibition may be a therapeutic strategy in PAH, but the effects of hormonal manipulation have not been tested in patients with pulmonary vascular disease.…”
mentioning
confidence: 99%
“…Metformin administration also decreased RVSP in Sugen/hypoxic‐induced PH rats (Dean et al . ) and Sugen‐treated Zucker fatty rats (Lai et al . ).…”
Section: Treatment Of Ph Using Medications For Metabolic Syndromesmentioning
confidence: 99%
“…However, there was no benefit of metformin therapy in older rats with established PH-HFpEF. In the female rat SuHx model of PH, metformin therapy reversed elevated P PA and vascular remodeling (56). In this study, metformin had several effects on SuHx lungs, including increased AMPK activity, decreased aromatase and estrogen levels and decreased PASMC proliferation, suggesting that one of the downstream effects of metformin-induced AMPK activation is to regulate the sex hormone axis via aromatase inhibition.…”
Section: K V 7 (Kcnq) Channel Activatorsmentioning
confidence: 59%